2020
DOI: 10.1186/s12889-020-08815-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between changes in HIV risk perception and condom use in East Zimbabwe 2003–2013: population-based longitudinal analyses

Abstract: Background: Perceiving a personal risk for HIV infection is considered important for engaging in HIV prevention behaviour and often targeted in HIV prevention interventions. However, there is limited evidence for assumed causal relationships between risk perception and prevention behaviour and the degree to which change in behaviour is attributable to change in risk perception is poorly understood. This study examines longitudinal relationships between changes in HIV risk perception and in condom use and the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 61 publications
(66 reference statements)
4
10
1
1
Order By: Relevance
“…Overall, just 12.7% of sexually active AGYW in this population had a high HIV risk perception. Factors independently associated with higher risk perception in this population are consistent with other published reports, including not using a condom at first sex 22,59 ; having ever had anal sex 60 ; and having an STI diagnosis, 61 multiple sexual partners, 41,62 and HIV-positive partner or partner with unknown HIV status 13,20,63 in the past 12 months. Notably, however, less than 30% of those diagnosed with an STI in the past 12 months and approximately one-half of those who reported having an HIV-positive sexual partner in the past 12 months reported having a high perceived risk of HIV.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, just 12.7% of sexually active AGYW in this population had a high HIV risk perception. Factors independently associated with higher risk perception in this population are consistent with other published reports, including not using a condom at first sex 22,59 ; having ever had anal sex 60 ; and having an STI diagnosis, 61 multiple sexual partners, 41,62 and HIV-positive partner or partner with unknown HIV status 13,20,63 in the past 12 months. Notably, however, less than 30% of those diagnosed with an STI in the past 12 months and approximately one-half of those who reported having an HIV-positive sexual partner in the past 12 months reported having a high perceived risk of HIV.…”
Section: Discussionsupporting
confidence: 90%
“…The observed mismatch between reported behaviors and perception of risk for HIV infection among sexually active AGYW is concerning because individuals with a lower perception of risk have been shown to be less likely to seek or use preventive measures, including HIV pre-exposure prophylaxis, 64 while continuing to engage in behaviors that can put them at risk for HIV infection. 22,23,65 Our study demonstrates that it is possible to identify AGYW who, despite having low risk perception, are at high risk of HIV infection, thereby opening the door for more effective counseling and interventions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Vale destacar que essa noção das vulnerabilidades permite a proposição de que políticas públicas podem impactar a prevenção do HIV, tendo em vista que apenas o conhecimento dos riscos não implica em mudanças de atitude e comportamentos, diante dos muitos fatores biopsicossociais que influenciam, como apontaram os achados de um estudo longitudinal realizado no Zimbábue 24 .…”
Section: Discussionunclassified
“…Condom use is long known to be effective and associated with safer sex among MSM (Klein & Kaplan, 2012 ). Shaefer et al (Schaefer et al, 2020 ) reported an association of high-risk perception of HIV and lack of condom use and also showed that an increase in condom use leads to a decrease in risk perception. However, a direct correlation between risk perception and real risk of HIV is highly complex (Plotzker et al, 2017 ), since other studies have shown that individuals at higher risk may perceive themselves at low or no risk of infection (Khawcharoenporn et al, 2019 ; MacKellar et al, 2007 ; Rutstein et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%